2021
DOI: 10.1371/journal.pone.0260021
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and efficacy of vaginal self-sampling for genital infection and bacterial vaginosis: A cross-sectional study

Abstract: Background & aim Screening for genital infection (GI) such as bacterial vaginosis (BV) and yeast infection, for sexually transmitted infection (STI), and for asymptomatic carriage of group B streptococcus (GBS) in pregnant women are common reason for medical appointments. The diagnosis and control of GIs, STIs, and GBS are major issues, for fertility and overall well-being of affected women. Conventional testing is performed using vaginal/cervical classical sampling (VCS); this procedure requires pelvic ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(53 citation statements)
references
References 52 publications
0
53
0
Order By: Relevance
“…The collection of a specimen for diagnosis can be performed using a speculum during the pelvic exam. When there is no reason for a pelvic exam as part of the clinical evaluation, a self-collected vaginal swab may also be provided ( Menard et al., 2012 ; Camus et al., 2021 ).…”
Section: Bacterial Vaginosismentioning
confidence: 99%
“…The collection of a specimen for diagnosis can be performed using a speculum during the pelvic exam. When there is no reason for a pelvic exam as part of the clinical evaluation, a self-collected vaginal swab may also be provided ( Menard et al., 2012 ; Camus et al., 2021 ).…”
Section: Bacterial Vaginosismentioning
confidence: 99%
“…Eighty per cent of studies (36 of 45) detected newly diagnosed positive CT/GC infections and 42.2% of studies (19 of 45) measured test accuracy 16 17 20 22–55. Seventeen studies reported 2×2 table values 22 28 30–33 35 36 38–43 51–53. We excluded four studies where reference test was unclear/not reported 22 31–33…”
Section: Resultsmentioning
confidence: 99%
“…Acceptability for SS was high (80.0%–100.0%; n=21) 28 30 32–35 41 42 44–46 49–52 55–60. Participants found SS easy (n=14) and comfortable (ie, painless; n=9), and would recommend it to others (n=3) 28 30 33 35 41 44–46 49 51 52 57–60.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations